Treehold - Swadling, W (Hart Publishing, 2023)
What property rights, if any, can exist with respect to standing trees? Is it possible to have a personal property right in a standing tree or even a freehold estate to the tree distinct from any title to the soil to which it is attached, what might be called a ‘Treehold’?